SYNTHESIS OF AND CHARACTERIZATION OF INDOLYL-1,8-NAPHTHYRIDIN-3-CARBONITRILES MOITIES (International Journal of Food and Nutritional Sciences, 2022)
In the present study novel synthesis of 2-amino-4-(2-methoxynapthylen-6’-yl)-6-(4-chlorophenyl)-pyridin-3-carbonitriles 1a and (5’-chloro-2’-phenyl-1H-indol-3’-yl)-acrylonitrile 2a underwent cyclization in presence of metallic sodium in refluxing 1,4-dioxane to afford 4-amino-5-(2’-methoxynaphthylen-6’-yl)-7-(4-chlorophenyl)-2-(5’-chloro-2’-phenyl-1H-indol-3’-yl)-1,8-naphthyridin-3-carbonitrile (3a-i) in good yield. The structures of all these unknown compounds have been confirmed with the help of physical data and spectral data like IR, 1H NMR and mass spectroscopy.